Efeito da adubação na qualidade do café: uma revisão de literatura - Corerato, Yago Lichtscheidl (Universidade Federal de São Carlos, 2023)
This work conducts a bibliographical survey to analyze the effects of fertilization on coffee quality. In the literature review, the interactions between fertilization, crop productivity and coffee quality were explored. The results highlight the influence of fertilization in determining the quality of coffee, which can directly affect the productivity and quality of the coffee drink. Each nutrient playing a role is equally important. Balance in the application of nutrients is essential, as fertilization impacts the quality of the final coffee. Attention to soil fertilization, with technical improvement, is essential to obtain high quality coffees. This work contributes to the understanding of the factors that influence coffee quality and shows that fertilization plays an important role in coffee quality.
Effect of fertilization on coffee quality: a literature review
Keywords: Adubação; Produção; Bebida café; Fertilizing; Production; Coffee drink; CIENCIAS AGRARIAS::AGRONOMIA